Effectiveness of Using Experimental Based Learning Videos on the Color Capillarity Phenomenon for Teachers at Aisyiyah II Kindergarten, Bengkulu City - Herawati, Sulikah Septi; Alimni, Alimni (UIN Fatmawati Sukarno Bengkulu, 2025)
This research aims to measure the effectiveness of using experimental-based learning videos on the color capillarity phenomenon for teachers at Kindergarten Aisyiyah II, Bengkulu City. This media is designed to improve teachers' abilities in conveying simple science material in an interactive and interesting manner. The research used qualitative research methods with the research subject being the Aisyiyah II Kindergarten teacher. Data was collected through observation, interviews and questionnaires. The research results showed that the effectiveness test through the teacher's pretest and posttest before and after watching the learning video showed an increase of 48.67% where the average score from the pretest was 46% to the posttest was 94.67%. The conclusion shows that the use of experimental-based learning videos on the color capillarity phenomenon for teachers at Kindergarten Aisyiyah II, Bengkulu City is effective in increasing teachers' understanding of simple science concepts, creativity in learning, and student involvement. This is supported by effectiveness test results data which shows a significant increase.